2007
DOI: 10.1097/01.aog.0000250535.97920.b5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress and Low Birth Weight Neonates in a Low-Income Population of Women

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(171 citation statements)
references
References 33 publications
7
160
1
3
Order By: Relevance
“…These biochemical changes end with placental hypo fusion and oxygen deficiency in fetus nutrition which may lead to preterm birth. 15,16 Poor and difficult health facilities are also a cause of depressive symptoms, and these maternal depressive symptoms sometimes play a role to admonish the search of health care facilities. 17 It's also challenging for Medical professionals differentiate the effect of depression and antidepressants on birth outcomes, most of studies investigate one thing not both.…”
Section: Resultsmentioning
confidence: 99%
“…These biochemical changes end with placental hypo fusion and oxygen deficiency in fetus nutrition which may lead to preterm birth. 15,16 Poor and difficult health facilities are also a cause of depressive symptoms, and these maternal depressive symptoms sometimes play a role to admonish the search of health care facilities. 17 It's also challenging for Medical professionals differentiate the effect of depression and antidepressants on birth outcomes, most of studies investigate one thing not both.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have examined food insecurity among pregnant women in other countries (27)(28)(29)(30). Laraia et al (2006) reported the rates of marginal food security (15%) and food insecurity (10%) among lowand moderate-income pregnant women, which were lower compared with the broader North Carolina population.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that pregnant women who suffer from chronic psychosocial stress 21 , who have ambivalent feelings with respect to the pregnancy 22 , or who have suffered some form of psychological, physical and/or sexual violence during pregnancy 23 have a greater chance of giving birth to an infant with a birth weight of less than 2,500 grams. Although these factors were not evaluated in this population of pregnant women, systematic incorporation of these forms of evaluation in routine prenatal care represents a challenge, particularly in less developed regions where these factors may contribute significantly towards the occurrence of low birth weight.…”
Section: Discussionmentioning
confidence: 99%